Effect of Gooseberry (Physalis angulata) Ethanol Extract in Wistar Rats Carrageenan-Induced Paw Oedema - Ami Nurlatifah; Eka Hendryanny; Yuniarti Yuniarti (Global Medical & Health Communication (GMHC), 2021)
Gooseberry is an herbaceous plant that contains flavonoids. Flavonoid is one of the secondary metabolites that have an anti-inflammatory effect. This study aims to determine the effect of using ethanol extract of gooseberry as an anti-inflammatory in carrageenan-induced paw edema. This study was in vivo experimental laboratory using a completely randomized design of 25 Wistar rats and divided into five groups. The negative control group was given carboxymethylcellulose. The positive control group has given diclofenac sodium 27 mg/200 gBW. The sample test group has given ethanol extract of gooseberry with 3.6 mg/200 gBW, 5.4 mg/200 gBW, and 7.2 mg/200 gBW dosage. Paw rat’s inflammation induced by injecting carrageenan and measured from 1st to 6th hour using a pletismometer. This study has conducted at Pharmacology Laboratory, Universitas Islam Bandung, and the Laboratory of Therapy and Pharmacology, Universitas Padjajaran, from June to September 2019. The result of average edema volume paw rats using the Kruskal-Wallis test on the 6th hour was p=0.02 (p<0.05). The Mann-Whitney test was p<0.05, showing differences between negative control and positive control and sample test groups. One-way ANOVA test on the percentage of edema inhibition between positive control and sample test group had p=0.107. It shows no significant difference. An effect of ethanol of extract of gooseberries as an anti-inflammatory with the highest percentage of edema inhibition is 5.4 mg/200 gBW dosage. The flavonoid content in gooseberries is thought to inhibit the formation of prostaglandins by inhibiting the cyclooxygenase enzyme. In conclusion, the ethanol extract of gooseberry can be anti-inflammatory. EFEK EKSTRAK ETANOL CIPLUKAN (PHYSALIS ANGULATA) TERHADAP EDEMA TELAPAK KAKI TIKUS GALUR WISTAR YANG DIINDUKSI KARAGENANCiplukan adalah tanaman herbal yang mengandung flavonoid. Flavonoid merupakan salah satu metabolit sekunder yang dapat memberikan efek antiinflamasi. Penelitian ini bertujuan mengetahui pengaruh penggunaan ekstrak etanol ciplukan sebagai antiinflamasi pada tikus yang diinduksi karagenan. Penelitian ini merupakan penelitian laboratorium eksperimental in vivo menggunakan desain rancangan acak lengkap pada 25 ekor tikus galur Wistar yang terbagi ke dalam lima kelompok. Kelompok kontrol negatif diberi carboxymethilcellulose. Kontrol positif diberi sodium diklofenak 27 mg/200 gBB. Kelompok uji diberi ekstrak etanol ciplukan dengan dosis 3,6 mg/200 gBB; 5,4 mg/200 gBB; dan 7,2 mg/200 gBB. Induksi inflamasi dilakukan dengan menginjeksikan karagenan pada telapak kaki tikus, lalu diukur menggunakan pletismometer dari jam ke-1 hingga jam ke-6. Penelitian ini dilakukan di Laboratorium Farmasi, Universitas Islam Bandung dan Laboratorium Farmasi dan Terapi, Universitas Padjajaran dari bulan Juni hingga September 2019. Volume rerata telapak kaki tikus pada jam ke-6 menggunakan Uji Kruskal-Wallis adalah p=0,02 (p<0,05). Hasil Uji Mann-Whitney diperoleh p<0,05 yang menunjukkan terdapat perbedaan bermakna antara kontrol negatif dan kontrol positif serta kelompok uji. Uji one-way ANOVA pada persentase penghambatan edema antara kontrol positif dan kelompok uji diperoleh p=0,107 yang menunjukkan tidak terdapat perbedaan yang bermakna. Terdapat pengaruh ekstrak etanol ciplukan sebagai antiinflamasi dengan persentase penghambatan edema tertinggi pada dosis 5,4 mg/200 gBB. Kandungan flavonoid pada ciplukan diduga mampu menghambat pembentukan prostaglandin dengan menginhibisi enzim siklooksigenase. Simpulan penelitian ini adalah ekstrak etanol ciplukan dapat digunakan sebagai antiinflamasi.